A wideband gain-enhanced dual-polarized printed antenna based on log-periodic parasitic directors (LPPDs). Issue 8 (23rd May 2016) - Ren, Y.-H.; Ding, J.; Guo, C.-J.; Song, Y.-C.; Qu, Y.
Abstract: A novel wideband and high gain dual-polarized antenna with log-periodic parasitic directors is presented in this paper. The antenna is composed of two cross printed dipole antennas vertically fixed on an aluminum plate as ground plane, which are excited by two similar micro-strip baluns. In order to further improve the gain with a broad bandwidth, the log-periodic parasitic directors are loaded on the printed dipole antennas innovatively. Measured results show that the proposed antenna achieves a –10 dB return loss with bandwidth of 1–2.1 GHz (71%), and its port isolation is higher than –20 dB within that band. Furthermore, the average gain of antenna is improved by 3 dB because of LPPDs.